Genetic Organization of Anabaenopeptin and Spumigin Biosynthetic Gene Clusters in the Cyanobacterium Sphaerospermopsis torquesreginae ITEP-024 - Lima, Stella T.; Alyarenga, Danillo.; Etchegaray, Augusto; Fewer, David P.; Jokela, Jouni; Varani, Alessandro M. [UNESP]; Sanz, Miriam; Dorr, Felipe A.; Pinto, Ernani; Siyonen, Kaarina; Fiore, Marli F. (Amer Chemical Soc, 2017)
Cyanobacteria produce a broad range of natural products, many of which are potent protease inhibitors. Biosynthetic gene dusters encoding the production of novel protease inhibitors belonging to the spumigin and anabaenopeptin family of nonribosomal peptides were identified in the genome of the bloom-forming cyanobacterium Sphaerospermopsis torques-reginae ITEP-024. The genetic architecture and gene organization of both nonribosomal peptide biosynthetic clusters were compared in parallel with their chemical structure variations obtained by liquid chromatography (LC-MS/MS). The spumigin (spu) and anabaenopeptin (apt) gene clusters are colocated in the genomes of S. torques-reginae ITEP-024 and Nodularia spumigena CCY9414 and separated by a 12 kb region containing genes encoding a patatin-like phospholipase, L-homophenylalanine (L-Hph) biosynthetic enzymes, and four hypothetical proteins. hphABCD gene cluster encoding the production of L-Hph was linked to all eight apt gene clusters investigated. here. We suggest that while the HphABCD enzymes are an integral part of the anabaenopeptin biosynthetic pathway, they provide substrates for the biosynthesis of both anabaenopeptins and spumigins. The organization of the spu and apt suggests a plausible model for the biosynthesis of the 4-(4-hydroxyphenyl)-2-acid (Hpoba) precursor of spumigin variants in S. torques-reginae ITEP-024 based on the acceptable substrates of HphABCD enzymes.